A Cross-Sectional Study of Depression in Rheumatoid Arthritis Patients at a Tertiary Care Center - Hansraj Parmar; Prakash Joshi; Reena Singh; Sachin Parmar; Ranjana Sharma (Journal of Pharmacy and Bioallied Sciences)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune condition often linked with depression, worsening symptoms, and lowering the quality of life. This study evaluated the prevalence of depression in female RA patients and its relationship with RA activity and inflammatory markers. Material and Methods: A cross-sectional study was conducted over 18 months, involving 185 female RA patients with depression, diagnosed using DSM-5 criteria. RA disease activity was assessed using the Disease Activity Score 28 (DAS 28), and inflammatory markers, including CRP, ESR, RF, and anti-CCP, were evaluated. Data analysis was performed using SPSS version 20.0. Results: Depression was present in 72.4% of patients, with mild, moderate, and severe depression observed in 31.4%, 26.5%, and 14.6%, respectively. Significant associations were found between depression severity and RA activity (P = 0.000). Elevated CRP and ESR levels were seen in 81.6% and 89.7% of patients, correlating with depression severity. Rheumatoid markers (RF and Anti-CCP) were also significantly linked to both RA activity and depression. Conclusion: High depression prevalence in RA patients, especially those with severe disease activity, highlights the need for integrated mental health and RA care to enhance patient outcomes.